1998
DOI: 10.1016/s0378-1097(98)00386-3
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular products as mediators of the formation and detachment of Pseudomonas fluorescens biofilms

Abstract: Pseudomonas fluorescens B52 produces substantial biofilms at the air/liquid/solid interface of glass coverslips clamped vertically and partly submerged in liquid medium at 21³C. Biofilm formation was maximal ca. 20^50 h after inoculation of the liquid medium and, as indicated by environmental scanning electron microscopy (ESEM), contained large numbers of bacterial cells that were embedded within an extensive exopolymeric matrix. Incubation beyond 50 h led to reductions in biofilm which ESEM related primarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
104
0
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 18 publications
6
104
0
4
Order By: Relevance
“…S9 (Wrangstadh et al, 1989). In P. fluorescens, starvation induced an increase in exopolysaccharide lyase production and biofilm dispersal (Allison et al, 1998), whereas in P. aeruginosa, alginate lyase activity was maximally induced in rapidly growing cells (Ott et al, 2001). Again, both of these observations suggest that increased biofilm dispersal rates may occur under both favorable and unfavorable conditions.…”
Section: Nutrient Cuesmentioning
confidence: 95%
“…S9 (Wrangstadh et al, 1989). In P. fluorescens, starvation induced an increase in exopolysaccharide lyase production and biofilm dispersal (Allison et al, 1998), whereas in P. aeruginosa, alginate lyase activity was maximally induced in rapidly growing cells (Ott et al, 2001). Again, both of these observations suggest that increased biofilm dispersal rates may occur under both favorable and unfavorable conditions.…”
Section: Nutrient Cuesmentioning
confidence: 95%
“…For example, the quorum signalling molecule, acyl-homoserine lactone (AHL), functions as a signal for the development of P. aeruginosa PA01 and Pseudomonas fluorescens B52 biofilms [36][37]. However, mathematical models based on O2 and nutrient transport (diffusion) limitation result in similar biofilm architecture (reviewed in [38]), suggesting biofilm development is equally sensitive to environmental conditions as it may be to geneticallydetermined regulation.…”
Section: Archetypal 'Flow-cell' Biofilmsmentioning
confidence: 99%
“…The flagellum-mediated swarming motility might be induced at this detachment process owing to the limited availability of nutrients, including iron, in the mature biofilm. Recent papers have suggested that each process of biofilm formation might be regulated by expression of quorum-sensing genes (1,9). These dynamic alternations in gene expression for biofilm formation might be regulated by the orf3 gene in relation to flagellum expression.…”
Section: Vol 188 2006mentioning
confidence: 99%